2014
DOI: 10.1080/09603123.2014.958134
|View full text |Cite
|
Sign up to set email alerts
|

Role of access to parks and markets with anthropometric measurements, biological markers, and a healthy lifestyle

Abstract: The results of this study suggest the importance of the role of environmental factors such as parks and markets in the development of cardiovascular risk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
1
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 30 publications
1
14
1
2
Order By: Relevance
“…Despite the lack of evidence of our results for obesity, other studies found an inverse relationship between the increased availability of green spaces and obesity [27]. We hypothesize two main reasons that could explain why we did not find an association between the density of green spaces and obesity.…”
Section: Comparison With Previous Studies and Mechanismscontrasting
confidence: 95%
See 1 more Smart Citation
“…Despite the lack of evidence of our results for obesity, other studies found an inverse relationship between the increased availability of green spaces and obesity [27]. We hypothesize two main reasons that could explain why we did not find an association between the density of green spaces and obesity.…”
Section: Comparison With Previous Studies and Mechanismscontrasting
confidence: 95%
“…Previous studies support the idea that greater availability of green spaces around home reduces blood pressure in adults [31,32], especially by harm reduction (e.g., exposure to noise or air pollution) [33], psychological and physiological stress alleviation, increased social cohesion, or physical activity [15]. Similarly, we found a relationship between green spaces and hypercholesterolemia, consistent with other previous studies [27,31,34], that suggested that green spaces could reduce cholesterol levels via physical activity, harm reduction or psychosocial pathways. However, we did not test the mediating pathways through which green spaces might reduce blood pressure or cholesterol levels.…”
Section: Comparison With Previous Studies and Mechanismssupporting
confidence: 92%
“…Most alarmingly, discretionary foods (often energy rich food and drinks high in saturated fats, sugars and/or salt) contributed 39% of energy intake for children and young people during 2011-2012 [103]. It is commonly accepted that diet plays a crucial role in chronic disease and obesity prevention and has been linked with environmental factors (e.g., distance to parks and markets) [79,105]. Due to lifestyle choices and the limitations of the current food system, obesity and chronic diseases will increasingly be a burden on the medical system and challenge the sustainability of cities.…”
Section: Urban Agriculture's Role In Food Securitymentioning
confidence: 99%
“…While green space and local biodiversity are associated with health and vitality [96][97][98] (and biodiversity losses/environmental degradation with ill-health [99][100][101]), these links require complex considerations. For example, closer residential proximity to green spaces and greater access to open spaces and safe, local parks, is associated with healthier dietary habits; however, this could be explained by experience through opportunity-more green spaces and parks may simply be a surrogate marker for lower density of fast-food outlets, convenience stores and an unhealthy food environment in general [102][103][104]. At this stage it is unknown if those scoring high on nature relatedness scales avoid ultra-processed foods, consume more fermented foods and/or maintain healthier dietary habits in general; however, a greater understanding of the emotional/cognitive drivers of a sustainable planetary health diet (a plant-based diet with minimal emphasis on animal products [105,106]) will require a closer look at nature relatedness.…”
Section: Building Nature Relatednessmentioning
confidence: 99%